An Analysis of Teaching Menstrual Care Skills Using Single-Subject Methodology: A Systematic Literature Review. - Kristiansen, Sarah; Syed, Noor; Anderson, Nathan; Bendush, Stephanie (Journal of Autism & Developmental Disorders, 2025)
Purpose: There is a paucity in research supporting procedures to teach skills needed during an individual's menstrual cycle. The purpose of this study was two-fold. First, a literature review was conducted to find publications on the topic of menstrual care. Second, the studies found were evaluated against What Works Clearinghouse™ (WWC) standards and analyzed to determine the presence of clinical components relevant to teaching these skills. Methods: A literature review was conducted according to PRISMA guidelines. The review identified publications that taught menstrual care skills to individuals diagnosed with autism spectrum disorder (ASD) or other disabilities. The review focused specifically on studies that employed single-subject research methodology. Studies found were analyzed against the WWC's criteria to assess the rigor of each studies' methodology. Finally, studies were categorized across indicators that are clinically relevant to teaching menstrual care skills. Results: The results highlighted a lack of empirical support for teaching menstrual care skills. 7 single-subject design studies were identified in the previous 40 years of research. One study met all criteria required to receive the WWC's highest rating. Conclusion: The complexity and private nature of menstrual care skills can make intervention development daunting. This paper was intended to provide menstrual care researchers with guidance in implementing high-quality studies. Additionally, scientist-practitioners can find guidance regarding important considerations to support programming that is both effective and respectful.